American journal of veterinary research - American Veterinary Medical Association (Chicago : American Veterinary Medical Association., 1940)
Vols. for 1956- include selected papers from the proceedings of the American Veterinary Medical Association.
Description based on:Vol.38,no.1(1977),title from vol.t.p.
Supplements accompany some numbers.
Microfiche.
Library has also printed format.
1
Keywords: Veterinary medicine -- Periodicals; Animals, Domestic -- Periodicals